CBSE (Commerce) Class 12CBSE
Share
Notifications

View all notifications
Books Shortlist
Your shortlist is empty

Solution for If Y = ( 1 + 1 X ) X , Then D Y D X = (A) ( 1 + 1 X ) X ( 1 + 1 X ) − 1 X + 1 - CBSE (Commerce) Class 12 - Mathematics

Login
Create free account


      Forgot password?

Question

If \[y = \left( 1 + \frac{1}{x} \right)^x , \text{ then} \frac{dy}{dx} =\]

(a) \[\left( 1 + \frac{1}{x} \right)^x \left( 1 + \frac{1}{x} \right) - \frac{1}{x + 1}\]

(b) \[\left( 1 + \frac{1}{x} \right)^x \log \left( 1 + \frac{1}{x} \right)\]

(c) \[\left( x + \frac{1}{x} \right)^x \left\{ \log \left( x + 1 \right) - \frac{x}{x + 1} \right\}\]

(d) \[\left( x + \frac{1}{x} \right)^x \left\{ \log \left( 1 + \frac{1}{x} \right) + \frac{1}{x + 1} \right\}\]

Solution

(a)  \[\left( 1 + \frac{1}{x} \right)^x \left( 1 + \frac{1}{x} \right) - \frac{1}{x + 1}\]

\[\text{Let y }= \left( 1 + \frac{1}{x} \right)^x \]
\[\text{ Taking log on both sides}, \]
\[\log y = x \log\left( 1 + \frac{1}{x} \right)\]
\[ \Rightarrow \frac{1}{y}\frac{dy}{dx} = x\frac{d}{dx}\log\left( 1 + \frac{1}{x} \right) + \log\left( 1 + \frac{1}{x} \right)\frac{d}{dx}\left( x \right) \]
\[ \Rightarrow \frac{1}{y}\frac{dy}{dx} = x\left( \frac{1}{1 + \frac{1}{x}} \right)\frac{d}{dx}\left( 1 + \frac{1}{x} \right) + \log\left( 1 + \frac{1}{x} \right)\]
\[ \Rightarrow \frac{1}{y}\frac{dy}{dx} = x \times \frac{x}{x + 1}\left( - \frac{1}{x^2} \right) + \log\left( 1 + \frac{1}{x} \right)\]
\[ \Rightarrow \frac{1}{y}\frac{dy}{dx} = \frac{x^2}{x + 1} \times \frac{- 1}{x^2} + \log\left( 1 + \frac{1}{x} \right)\]
\[ \Rightarrow \frac{1}{y}\frac{dy}{dx} = \frac{- 1}{x + 1} + \log\left( 1 + \frac{1}{x} \right)\]
\[ \Rightarrow \frac{dy}{dx} = y\left[ \frac{- 1}{x + 1} + \log\left( 1 + \frac{1}{x} \right) \right]\]
\[ \Rightarrow \frac{dy}{dx} = \left( 1 + \frac{1}{x} \right)^x \left[ \log\left( 1 + \frac{1}{x} \right) - \frac{1}{x + 1} \right]\]

 

  Is there an error in this question or solution?

Video TutorialsVIEW ALL [1]

Solution If Y = ( 1 + 1 X ) X , Then D Y D X = (A) ( 1 + 1 X ) X ( 1 + 1 X ) − 1 X + 1 Concept: Simple Problems on Applications of Derivatives.
S
View in app×